2019
DOI: 10.1016/j.chaos.2019.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Multifractal properties of sample paths of ground state-transformed jump processes

Abstract: We consider a class of Lévy-type processes with unbounded coefficients, arising as Doob h-transforms of Feynman-Kac type representations of non-local Schrödinger operators, where the function h is chosen to be the ground state of such an operator. First we show existence of a càdlàg version of the so-obtained ground state-transformed processes. Next we prove that they satisfy a related stochastic differential equation with jumps. Making use of this SDE, we then derive and prove the multifractal spectrum of loc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…For the operators ( 5)-( 6) and more general non-local Schrödinger operators, ground state transformed processes and related stochastic differential equations with jumps have been analysed in [28]. It is, however, in general not trivial to obtain the necessary regularity of φp and the existence of a solution of (8) needs a proper study.…”
Section: Resultsmentioning
confidence: 99%
“…For the operators ( 5)-( 6) and more general non-local Schrödinger operators, ground state transformed processes and related stochastic differential equations with jumps have been analysed in [28]. It is, however, in general not trivial to obtain the necessary regularity of φp and the existence of a solution of (8) needs a proper study.…”
Section: Resultsmentioning
confidence: 99%
“…(1) As shown in [27,Th. 3.1], under the condition that x → ∇ log ϕ 0 (x) is locally bounded, a GST process ( X t ) t≥0 satisfies the SDE given in (1.4).…”
Section: 2mentioning
confidence: 99%
“…A first variant for jump processes has been obtained in [16,Th. 5.1] for GST processes derived from isotropic stable processes, but the argument is generic and it applies directly to the present settings, see for further details [27,Th. 2.1].…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…Simsekli et al (2020a) identified the complexity of the fractals generated by a Feller process that approximates SGD. The intrinsic complexity of a fractal is typically characterized by a notion called the Hausdorff dimension (Le Guével, 2019;Lőrinczi and Yang, 2019), which extends the usual notion of dimension to fractional orders. Due to their recursive nature, Markov processes often generate random fractals (Xiao, 2003).…”
Section: Generalization -Hausdorff Dimension and Tail Index Analysismentioning
confidence: 99%